Gambaran Kepercayaan Diri pada Remaja Yang Mengalami Kekerasan Seksual di Desa X - Husnul Yanti; Elis Suci Prapita Sari Abdullah (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2021)
Self-confidence is an important thing that must be owned by someone so that they can see their level of high courage, social relations, responsibility and self-esteem. This also applies to individuals who have experienced sexual violence. This study aims to determine the description of self-confidence in adolescents who experience sexual violence in X Village. The method of data collection in this study used interviews. The subjects in this study were 2 teenagers who had experienced sexual violence and were between the ages of 12-15 years. The results showed that the two subjects had different self-confidence, this was seen from the fulfillment of the aspects of self-confidence experienced by the subject, there are self-ability, optimism, responsibility, rational and realistic, and objectivity. The existence of support from family and the surrounding environment can form confidence in subjects who have experienced sexual violence